Social competence and access to finance in Financial institutions- an empirical study of Small and medium enterprises in Uganda - Kamukama, Nixon (American Journal of Finance, 2020)
Purpose: The paper examined the mediating effect of innovation in the relationship between social competence and access to finance by Small and Medium Enterprises (SMEs) in Uganda. The major aim was to establish the role of innovation in the relationship between social competence and access to finance. Methodology: The research took a positivist paradigm and a cross-sectional research design were used to collect data from 307 SMEs in Uganda. Close-ended and self-administered questionnaire with question items anchored on a five-point Likert-type scale was used to collect data from either managers or owner of SMEs. Pearson correlation and Hierarchical regression analyses were employed for data analysis. More so, the study adopted MedGraph program, Sobel tests, Kenny, and Baron Approach to test for mediation effects. Findings: The findings indicated that the true drivers of access to finance by SMEs in Uganda are social competence and innovation. However, innovation exhibits partial form of mediation in the relationship between social competence and access to finance. Unit Contribution to practice and policy: Since innovation was found to be a causal chain in the relation between social competence and access to finance in this study, managers of the SMEs should endeavor to reinforce agents of innovation since commercial institutions trade off higher interest and lower collateral requirements for firms involved in the innovative process. Besides, this study can therefore reinforce the importance to foster academic achievement not only because of academic and learning reasons, but also because of its implications in other important domains (such as social competence) of young generation development along the school years. The government of Uganda can therefore, introduce some subjects in schools and institutions that can promote the development of social competences in the learning group. Study Limitation: First, only a single research methodological approach was employed and future research through interviews could be undertaken to triangulate. More so, future studies could use the same basic hypotheses and regression construction, but implement the study in terms of a longitudinal rather than a cross-sectional design. The longitudinal study would need to correct changes in data relative to time element.
Keywords: Social Competence; Innovation; Small and Medium Enterprises (SMEs); Mediating effect; Access to Finance